S’approprier la « frontière » et invisibiliser l’immigré dans la fabrique urbaine de Nicosie Sud - Marion Sabrié (Territoire en Mouvement)
Since the Turkish invasion of 1974, the southern part of the old town of Nicosia, the capital of Cyprus, has been abandoned by its Greek-speaking inhabitants because it recalled this painful past. Therefore, few immigrant communities settled there. Since the opening in 2003 of two crossing points of the Green Line in the heart of the old town, the latter is again tamed by the Greek Cypriots. The transition from the front (and the latent conflict) to the pacified separation line explains this taking back of the old city center. Based on sixty semi-structured interviews with Nicosians, conducted between 2015 and 2018, this article analyzes how the appeasement of the Cypriot conflict in Nicosia, the construction of peace by the urban coexistence and the ongoing metropolisation of the capital city, accelerated by Cyprus adhesion to the European Union in 2004, push Greek Cypriots to reinvest a for a long time repulsive city center, displacing its disadvantaged immigrant populations towards the peripheries. The different processes mentioned, as well as the "tourism development" around the Buffer zone or "showing conflictuality" (Gœury, 2008), are concomitant with an unconscious strategy of erasure or displacement of the non-Greek speaking groups. If the visible/invisible duality can be applied to the Green Line, it is more complex when it comes to communities. Immigrants are gradually becoming invisible through slow gentrification, while the Greek Cypriots are moving back into the southern old city. Urban reconciliation between the Greek Cypriot and Turkish Cypriot communities is therefore at the expense of the immigrants.